Digital media and the entrenchment of right-wing populist agendas - Schroeder, R (SAGE Publications, 2019)
Since Brexit and the election of President Donald Trump, news media around the world have given extensive coverage to the issue of disinformation and polarization. This paper argues that while the negative effects of social media have dominated the discussion, these effects do not address how right-wing populists have been able successfully and legitimately to use digital media to circumvent traditional media. The paper uses the United States and Sweden as case studies about how digital media have helped to achieve electoral success and shift the political direction in both countries - though in quite different ways. It also argues that the sources of right-wing populism go beyond the hitherto dominant left-right political divide, capturing anti-elite sentiment and promoting exclusionary nationalism. The dominance of the issue of media manipulation has obscured the shift whereby the relation between the media and politics has become more fluid and antagonistic, which fits the populist agenda. This shift requires a rethinking of political communication that includes both the social forces that give rise to populism and the alternative digital channels that entrench them, with implications for the prospects of the role of media in politics in the two countries and beyond.